The American Board of Colon and Rectal Surgery: Past, Present, and Future - Schoetz, David J., Jr. (Clinics in Colon and Rectal Surgery, 2012)
Since the incorporation of the American Board of Proctology, development and refinement of the process of board certification has been a critical part of the establishment and growth of the specialty of colon and rectal surgery. Continued commitment to the process begun by the early pioneers of this field provides quality practitioners not only when initially trained, but increasingly throughout the continuum of each diplomate's professional career. Board certification and maintenance of certification are the most tangible examples of our commitment to our patients and the public.
Keywords: ABCRS; certification; maintenance of certification